Self-management of chronic, non-communicable diseases in South Asian settings: A systematic mixed-studies review. - Faraz Siddiqui; Catherine Hewitt; Hannah Jennings; Karen Coales; Laraib Mazhar; Melanie Boeckmann; Najma Siddiqi (Public Library of Science (PLoS), 2024)
Self-management is crucial in mitigating the impacts of a growing non-communicable disease (NCD) burden, particularly in Low and Middle-Income countries. What influences self-management in these settings, however, is poorly understood. We aimed to identify the determinants of self-management in the high NCD region of South Asia and explore how they influence self-management. A systematic mixed-studies review was conducted. Key electronic databases [MEDLINE (1946+), Embase (1974+), PsycInfo (1967+) and CINAHL (EBSCOhost)] in March 2022 (and updated in April 2023) were searched for studies on the self-management of four high-burden NCD groups: cardiovascular diseases, type 2 diabetes, chronic respiratory diseases and depression. Study characteristics and quantitative data were extracted using a structured template, and qualitative information was extracted using NVivo. Quality appraisal was done using the Mixed Methods Assessment Tool (MMAT). Quantitative findings were organised using the Commission on Social Determinants of Health (CSDH) framework and synthesised narratively, supported by effect direction plots. Qualitative findings were thematically synthesised. Both were integrated in a mixed synthesis. Forty-four studies (26 quantitative, 16 qualitative and 2 mixed-methods studies) were included, the majority of which were conducted in urban settings and among individuals with diabetes and cardiovascular diseases. Higher age, education, and income (structural determinants), health-related knowledge, social support and self-efficacy (psychosocial determinants), longer illness duration and physical comorbidity (biologic determinants), and the affordability of medicine (health-system determinants) were key determinants of self-management. Qualitative themes highlighted the role of financial adversity and the social and physical environment in shaping self-management.A complex interplay of structural and intermediary social determinants shapes self-management in South Asian settings. Multi-component, whole-systems approaches could boost self-management in these settings. Key areas include empowerment and education of patients and wider community, design and delivery of bespoke behavioural interventions and a stronger emphasis on supporting self-management in healthcare settings.